[3]Rotaxanes with Mixed Axles: Polyynes and Cumulenes - Franz, Michael; Januszewski, Johanna; Hampel, Frank; Tykwinski, Rik R. (European Journal of Organic Chemistry, 2019)
Tailoring synthetic strategies toward complex, but well-defined, molecular architectures is an important aspect of Today's organic chemistry. Herein, we present designs to build up [3]rotaxanes of Type 2.1 and Type 3 that feature both a polyyne and a cumulene axle in a single mechanically interlocked molecule. The combination of two sp-hybridized carbon chains was achieved by functionalization of a phenanthroline-based macrocycle, which allowed the coupling of two [2]rotaxanes toward Type 3 [3]rotaxanes with two polyynes, two cumulenes, or one polyyne and one cumulene axle. The structures have been established by NMR and UV/Vis spectroscopies, as well as high-resolution mass spectrometry. A [3]rotaxane of Type 3, featuring two [9]cumulene axles, has been assembled and spectroscopically characterized despite expectations that it would be unstable. This represents only the second cumulene rotaxane reported to date. All designs and attempts to form [3]rotaxanes of Type 2.1, which combine a polyyne and cumulene threaded through a single macrocycle, have been unsuccessful.
CRIS-Team Scopus Importer:2019-06-21
Keywords: Carbon atomic wire; Cumulenes; Mechanical bond; Polyynes; Rotaxanes

Cumulene Rotaxanes: Stabilization and Study of [9]Cumulenes - Franz, Michael; Januszewski, Johanna; Wendinger, Dominik; Neiß, Christian; Movsisyan, Levon D.; Hampel, Frank; Anderson, Harry L.; Görling, Andreas; Tykwinski, Rik (Angewandte Chemie International Edition, 2015)
The stabilization of long [n]cumulenes has traditionally been achieved by placing sterically bulky protecting groups at the termini, which shield the reactive carbon chain from unwanted reactions. Herein, we present an alternative strategy: stabilization through threading the sp-hybridized carbon chain through a phenanthroline-based macrocycle. The result is stable [9]cumulene rotaxanes that enable the study of properties as a function of length for [n]cumulenes in unprecedented detail, including by quantitative UV/Vis spectroscopy, cyclic voltammetry, and differential scanning calorimetry. The experimental results are supported by DFT calculations.
Keywords: carbynes; cumulenes; dispersion forces; electrochemistry; rotaxanes

Synthesis of polyyne rotaxanes - Movsisyan, Levon D.; Kondratuk, Dmitry V.; Franz, Michael; Thompson, Amber L.; Tykwinski, Rik; Anderson, Harry L. (Organic Letters, 2012)
Active-metal templating has been used to synthesize rotaxanes consisting of a phenanthroline-based macrocycle threaded around a C8, C12, or C20 polyyne chain. The crystal structure of the C12 rotaxane has been determined. In the rhenium(I) carbonyl complex of this rotaxane, with Re(CO) Cl coordinated to the phenanthroline macrocycle, the proximity of the polyyne chain quenches the luminescence of the rhenium. These rotaxanes offer a new approach to controlling the environment and interactions of a polyyne chain. © 2012 American Chemical Society.